1994
DOI: 10.1159/000176464
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic Impact of Diuretic Therapy in Chronic Heart Failure

Abstract: An immediate improvement in haemodynamic variables and cardiac performance is achieved in chronic heart failure following diuretic therapy, primarily due to reductions in plasma and extracellular fluid volumes. Humoral markers of these alterations are increased plasma renin, angiotensin and aldosterone levels; these increase maximally over the ñrst week of treatment but attenuate during sustained therapy. There are reciprocal alterations in plasma α-atrial natriuretic peptide levels. These findings suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…Studies of human patients with CHF who were treated with bumetanide showed considerable improvement of clinical signs, both at rest and on exertion, without blood electrolyte changes. 9,10 Similar findings have been partially confirmed in dogs. 11 ACEI have two major functions in CHF: prevention of vasoconstrictive effects of angiotensin II in veins and arteries and reduction of sodium and water retention through inhibition of aldosterone release.…”
supporting
confidence: 63%
“…Studies of human patients with CHF who were treated with bumetanide showed considerable improvement of clinical signs, both at rest and on exertion, without blood electrolyte changes. 9,10 Similar findings have been partially confirmed in dogs. 11 ACEI have two major functions in CHF: prevention of vasoconstrictive effects of angiotensin II in veins and arteries and reduction of sodium and water retention through inhibition of aldosterone release.…”
supporting
confidence: 63%
“…Some explanations can be proposed for the presence of the deleterious effect of diuretics on renal function in critically ill patients with sepsis/septic shock: a) reduction in preload with renal vasoconstriction, activation of the renin-angiotensin-aldosterone system and sympathetic stimulation (this reduction in preload occurs not only by increased urine output induced by furosemide, but also by a prostaglandin-mediated venodilation) (34,35); b) Dobrowolski et al (36,37) demonstrated a pronounced decrease in medullary blood flow compared to the cortex after administration of furosemide. The differential effect of furosemide on cortical and medullary blood flow may increase the intrarenal risk of medullar ischemia, favoring the development of acute tubular necrosis (36-38).…”
Section: Discussionmentioning
confidence: 99%
“…[20] Loop diuretics given intravenously also have an immediate effect in reducing preload by causing venous dilatation, increasing venous capacitance, and reducing cardiac preloadJ19-21] [20] Loop diuretics given intravenously also have an immediate effect in reducing preload by causing venous dilatation, increasing venous capacitance, and reducing cardiac preloadJ19-21]…”
Section: Efficacy Of Torasemide In the Treatment Of Congestive Heart mentioning
confidence: 99%